The Impact of Artificial Intelligence on Students' Learning Motivation in the Digital Era - Nur ‘Azizah; Insan Roudloh; Selnistia Hidayani (PT. Intelek Cendikiawan Nusantara, 2025)
The use of artificial intelligence (AI) in higher education has increased with the advancement of digital technology. Students utilize various AI applications, including ChatGPT, Google Gemini, and Grammarly, to master course material, complete academic assignments, and improve the quality of academic writing. This study aims to evaluate how students use AI and its impact on learning motivation in the digital era. The research approach uses a qualitative descriptive method through a literature review, examining journal articles, research reports, and related scientific materials published over the past five years. Data processing techniques include data simplification, data presentation, and inference. The study findings indicate that the use of AI produces positive effects, such as increased learning efficiency, material understanding, autonomy, and student learning motivation. However, uncontrolled application of AI can also trigger negative impacts, such as excessive addiction, decreased internal motivation, and the risk of violating academic ethics. Therefore, this study emphasizes the need for digital literacy, ethical awareness, and pedagogical integration of AI so that the technology can maintain student learning motivation optimally and sustainably.